Stratificare socială în România: o analiză de clase latente - Vasile, Octavian-Marian (Calitatea Vieții, 2008)
Every society knows some level of inequality. The literature about types of stratification is extensive, showing that an individual has at least a different social position from the others; in other words, the individuals can belong to a social class and/or can have a social status. In this article I want to test the integrative social structure schema proposed by Anthony Giddens (1997) on the case of Romania, and to see how it is stratified. For the analysis I used Public Opinion Barometer (Soros Foundation Romania) from October, 2005. I used latent class analysis and the specific statistical software Latent Gold 4.0. The results partially confirm Giddens’ model on the case of Romania, showing, at the same time, that the Romanian society is stratified. Social structure theory and methodology well-known and accepted by scholars in stable social systems should be critically discused and adapted to the Romanian case.